1976
DOI: 10.1111/j.1348-0421.1976.tb00907.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive Effect of Bacterial Lipopolysaccharide on Antibody Response

Abstract: Injection of endotoxins (bacterial lipopolysaccharide: LPS) several days prior to immunization causes the suppression of antibody response. The suppressive effects of several kinds of LPS preparations on the plaque-forming cell (PFC) antibody response in the spleen of mice were examined after immunization with sheep red blood cells (SRBC). Glycolipids obtained from heptoseless mutants (Re form) of salmonella or its lipid A preparation coupled artificially with bovine serum albumin (BSA) are capable, like LPS o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
2

Year Published

1977
1977
1992
1992

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
1
10
2
Order By: Relevance
“…However, the modulation pattern of the antibody-forming cell response in mice by M . xanthus myxospores was quite different from that reported for the LPS from Gram-negative bacteria (Diamantstein et al, 1976;Nakano et al, 1976;Covert & Zarkower, 1971). Furthermore, no LPS has been described among the components of myxospore cells (Sutherland, 1976).…”
Section: Discussioncontrasting
confidence: 60%
“…However, the modulation pattern of the antibody-forming cell response in mice by M . xanthus myxospores was quite different from that reported for the LPS from Gram-negative bacteria (Diamantstein et al, 1976;Nakano et al, 1976;Covert & Zarkower, 1971). Furthermore, no LPS has been described among the components of myxospore cells (Sutherland, 1976).…”
Section: Discussioncontrasting
confidence: 60%
“…However, the endotoxin may act on the immune response in several ways. It is known that the effects of endotoxin on antibody response are dependent upon the timing of injection of LPS and antigen : the response is suppressed when LPS is given before (7,21) or following (4) the antigen, while LPS injected at the same time as antigen may result in immunopotentiation (7,11,21). Furthermore, Kanamori (17) reported that LPS from Y. enterocolitica enhanced the antibody response when injected simultaneously with a protein antigen, and Kawaoka et al (18) showed that the yield of LPS is decreased and its composition different when Y. enterocolitica is grown at 37 C in comparison with 25 C-grown cultures.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of either of the opposite effects depended upon the timing of administration with antigens and adjuvants and other factors such as dose of antigen and adjuvant and the time of assay, as indicated by our results and the results of Warr and Sljivic (26). The immunosuppressive effect was also reported for other adjuvants such as LPS of Salmonella typhimurium by Nakano et al (15). The immunosuppression, however, appears not to be a common feature among the activities of various adjuvants, since yeast cell wall, zymosan, LPS of E. coli, B. pertussis and BCG did not exhibit immunosuppressive effects when given 14 days before antigen injection (Table 5).…”
Section: Discussionmentioning
confidence: 70%